Comparison of Job Burnout among Emergency Medicine, Surgery, Internal Medicine, Obstetrics and Gynecology and Pediatrics Residents at the First year of residency program - Basir Ghafouri, Hamed; Tabibzadeh Dezfoouli, Seyedamir; Abazarian, Niloofar; Mohammadreza Mirkarimi, Seyed; Mohammadi, Fatemeh; Rezai, Mahdi (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Considering the importance of burnout and its consequences and the lack of studies on the prevalence of burnout among medical residents in our country, a study was conducted to investigate and compare burnout among emergency medicine, surgery, internal medicine, gynecology, and pediatric residents.Methods: This study was carried out in an observational-analytical manner in three universities of medical sciences. The Maslach Burnout Inventory questionnaire was used to assess the medical residents at the beginning and the end of the first year of residency. The demographic information, including age, gender, and marital status, was also asked. Statistical analysis was performed using SPSS 22.Results: The burnout was shown to increase significantly among emergency medicine residents (P = 0.015), surgery residents (P = 0.043), and pediatrics residents (P = 0.021) at the end of the first year of their residency program. However, there was not a meaningful difference between burnout scores at the beginning and the end of the first year for internal medicine (P = 0.643) and gynecology (P = 0.849) residents. There was also a significant difference between the scores of burnout between different academic residents (P = 0.036). Emergency medicine, surgery, and pediatric residents had higher burnout rates.Conclusion: Burnout out is common in emergency Medicine, surgery, pediatrics, internal medicine, and gynecology residents, but vary according to the field of their study